The empowered child in the absence of father a critical discourse analysis of Ayroso's mister world and his magical box and De Vera's tatay, through the winds and waves - Sayuno, Cheeno Marlo M. (2017)
The important role of a father is usually addressed in short stories for children in an attempt to make child readers find comfort in reading materials that deal with the same problems that they might be facing as children of Overseas Filipino Workers, or even as children who have lost their fathers, temporarily or permanently.
Through Fairclough's Critical Discourse Analysis, this article studies how the child is empowered despite the abscence of the father using Alelie Dew Ayroso's Mister World and His Magical Box and Georgianna de Vera's Tatay, Through the Winds and Waves as samples of stories tackling the said issue by tapping into the sensibilities of child characters who are enpowered in facing the struggles of a fatherless life.
Based on the analyses, the child protagonist are described to posses certain physical, social, and psychological characteristics that prepare them to take a central role in empowerment despite the situations that they face as children. These children are exceptional in dealing with the conflict because they are set to be role models especially for children who might be having the same experience.
The study thus forwards the character that a Filipino child is able to maintain despite issues of overseas employment hoping that this could be imbibed by the child readers as well.
Keywords: Filipino foreign workers; Filipino Children empowerment